The effects of Antarctic alteration and sample heterogeneity on Sm-Nd and Lu-Hf systematics in H chondrites. (15th July 2021) - Maeda, Ryoga; Goderis, Steven; Debaille, Vinciane; Pourkhorsandi, Hamed; Hublet, Geneviève; Claeys, Philippe
Abstract: Long-lived radioactive isotope systematics, such as Sm-Nd and Lu-Hf, are useful tools as important chronometers and tracers for chemical differentiation processes. Even though Antarctic meteorites include rare meteorites such as ungrouped meteorites, the effects of Antarctic alteration on the Sm-Nd and Lu-Hf systems in chondrites have not yet been evaluated in detail. Moreover, the heterogeneity of Sm-Nd and Lu-Hf data in bulk chondrites prevents the determination of precise average Sm-Nd and Lu-Hf values ( e.g., for individual chondrite groups). To examine the effects of Antarctic alteration and sample heterogeneity on the Sm-Nd and Lu-Hf isotope systematics, ten Antarctic H chondrites (HCs) and three HCs from hot deserts were characterized for their modal abundances, elemental abundances, and Sm-Nd and Lu-Hf isotopic compositions. Regardless of the classical weathering index for Antarctic meteorites and the normalized Rb abundance used as a chemical alteration indicator in this study, the modal and elemental abundances in Antarctic HCs appear to be in good agreement with those in non-Antarctic HCs. The Sm-Nd and Lu-Hf isotopic compositions of the characterized H chondrites fall within the range measured for both HC falls and for falls of other chondrite groups, except in the case of the most heavily altered sample. Consequently, the effects of Antarctic alteration processes on the Sm-Nd and Lu-Hf systematics in HCs appear to be limited, except in the case of Asuka 09516. The latter meteorite exhibits severe mineralogical and chemical alteration, with considerable losses of even the rare earth elements (REEs), which are considered relatively immobile. The 147 Sm/ 144 Nd, 143 Nd/ 144 Nd, 176 Lu/ 177 Hf, and 176 Hf/ 177 Hf of bulk HCs correlate with their P/Mg and Y/Mg. Furthermore, the Lu-Hf ratios correlate strongly with their P/Ca and Y/Ca as well as their P/Mg and Y/Mg. Thus, the distribution of the elements between constituent minerals in ordinary chondrites (OCs) may control the heterogeneity observed for the bulk Sm-Nd and Lu-Hf data. In this context, the weight ratio of Ca-phosphates to Ca-pyroxene, or at least that of Ca-phosphates to silicates, may be a key factor leading to the observed elemental and isotopic variations. This observation indicates that the nugget effect of Ca-phosphates in OCs as the result of insufficient homogenization or terrestrial alteration leads to the heterogeneities displayed by the Sm-Nd and Lu-Hf data. Moreover, it also indicates that the use of equilibrated OCs for the determination of Sm-Nd and Lu-Hf data is affected more by sample heterogeneity, especially with respect to Ca-phosphates, than is the case for unequilibrated OCs, based on the re-distribution of REEs during thermal metamorphism on their parent bodies. This study demonstrates that Antarctic meteorites commonly preserve their original Sm-Nd and Lu-Hf isotopic compositions as much as chondrite falls, although exceptions are possible in the case of severe alteration. Similar to previous studies, we recommend the use of unequilibrated chondrites, for which the re-distribution of REEs is less extensive, for the determination of well-constrained average Sm-Nd and Lu-Hf isotopic compositions for individual chondrite groups as well as their robust Chondritic Uniform Reservoir values.